Transcript level of an andrographolide-biosynthesis gene (hmgr) of Andrographis paniculata subjected to salinity treatment - Ismail, Nor Adibah; Phang, Ing Chia; Darnis, Deny Susanti (2014)
High demand of medicinal plants for traditional treatment and development of pharmaceutical products have attracted Malaysia to become a key herbal medicine producer for global and local usage. One of the Malaysian herbs which have a strong potential to be commercialized is Andrographis paniculata (King of bitters/Hempedu Bumi). This medicinal plant is well known for its therapeutical compound, diterpene lactones (andrographolide). Soil salinity is one of the major problems affecting agricultural sector worldwide because as salt accumulates in soil, plant productivity decreases. Generally, the higher the NaCl concentration, the greater the symptoms of salinity stress. These include browning of leaves and dehydration. One of the genes involved in biosynthesis of andrographolide in A. paniculata is 3-hydroxy-3-methylglutaryl-coenzyme A reductase (hmgr). Thus, the present study was conducted to investigate the transcript level of hmgr of A. paniculata grown under salinity condition. Primer pairs for hmgr have been designed, and the expression level of hmgr was quantified using a quantitative real time polymerase chain reaction (qPCR). First, RNA from A. paniculata leaves treated in different salinity concentrations including control was isolated and then converted to cDNA. From qPCR study, it is found that hmgr gene was up- regulated by 3.165-, 3.302-, and 3.473-fold in A. paniculata treated with 20.55, 41.1, and 66.75 mM NaCl, respectively, in comparison to the control. Salt may trigger the signalling network by up-regulating the hmgr expression level in plants. Andrographolide content is expected to correlate with the hmgr transcript level under saline condition. Determination of andrographolide content using HPLC is currently underway. Further details on the effect of salinity on the gene expression level of hmgr will be elucidated in the conference.